2003
DOI: 10.1186/1751-0147-44-s1-p56
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Oxacillin in Serum and Milk of Treated and Untreated Quarters in Cows Following Intramammary Infusion*

Abstract: Experience in the use of intramammary antibiotic therapy has indicated that antibiotics are absorbed from the treated quarters into systemic circulation; degrees of absorption and hence crossover of drug to untreated quarters being different for different antibiotics. To answer these questions, a study was conducted on the use of oxacillin in three lactating cows of German Black Pied breed. The health status of quarters was assessed as per IDF criteria. Two quarters of each cow were infused each with Injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, oxacillin is absorbed twice as rapidly as benzylpenicillin (Ziv and Sulman, 1974). Oxacillin is absorbed quickly and appears in blood serum as early as 10 min post administration (Bansal et al, 2003). On the other hand, cefacetrile sodium cannot be detected in blood plasma even after 10 h following single intramammary infusion of 235 mg of cefacetrile sodium per quarter in lactating dairy cows (Carli et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…For example, oxacillin is absorbed twice as rapidly as benzylpenicillin (Ziv and Sulman, 1974). Oxacillin is absorbed quickly and appears in blood serum as early as 10 min post administration (Bansal et al, 2003). On the other hand, cefacetrile sodium cannot be detected in blood plasma even after 10 h following single intramammary infusion of 235 mg of cefacetrile sodium per quarter in lactating dairy cows (Carli et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the drug concentration in milk from the treated quarters at first milking PLI ranged 8.25 to 12.0 μg/ml in G2 and 26.83 to 37.61 μg/ml in G3. This marked variability is a typical phenomenon frequently observed with other antibiotics too, such as oxacillin (Bansal et al 2003) and ceftiofur (Smith et al 2004). The reasons for this are multiple and include udder health (pH affecting ionization and therefore passage via the bloodmilk barrier), the amount of connective tissue present in udder that hampers proper distribution, lactation stage, milk production levels, the milking frequency/milking interval and the udder tissue binding that lead to uneven distribution (Gehring and Smith 2006;Knappstein et al 2006).…”
Section: Discussionmentioning
confidence: 65%
“…A similar observation was recorded by Nouws and Ziv (1979) who found that following single intramammary administration of 1,200 mg of erythromycin in lactating cows, drug was well distributed in the various body tissues such as liver, kidney and muscles. Further, the passage rates to systemic circulation seem to vary with the antibiotic, e.g., oxacillin: 64% to 82% (Bansal et al 2003) and cephapirin: 30% to 40% (Stockler et al 2009). Knappstein et al (2006) expressed this drug disposition pattern in terms of the milk to serum concentration ratios; great differences were shown to occur between antibiotics and in relation to the udder health.…”
Section: Discussionmentioning
confidence: 99%